Repair of a dehiscence defect in an intra-osseous dental implant using a synthetic matrix bone graft and a home-use intraoral photobiomodulation device: Case report - Hing, Alan K.; Hamblin, Michael R. (Hasanuddin University, 2024)
A variety of techniques and materials have been used to improve the structural base of osseous tissue for supporting dental implants. However, there are not many articles describing techniques to address bone loss around an implant that had been integrated for a period of time but then lost the bony support around one or more walls forming a dehiscence defect. The following clinical case report demonstrates the use of a home-use intraoral photobiomodulation device (PBM Implant) in combination with a synthetic matrix bone graft to repair a dehiscence defect. Another novelty in this case, is the type of dental implant employed, called an intraosseous implant screw that stabilizes a tooth, which was a technique commonly employed over 30 years ago.